2016
DOI: 10.2507/ijsimm15(4)co15
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Demand Reshaping and Substitution Effects of Probabilistic Selling

Abstract: This paper addresses the effect of probabilistic selling on inventory decisions and the expected profit through demand reshaping and demand substitution. By considering a scenario with two higher-priced specific products and one lower-priced probabilistic product, we construct a new newsboy-type inventory model with demand reshaping and substitution. A simulation study is implemented to explore extensively the effects of demand uncertainty, demand correlation, price sensitivity and price discount on the invent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Endogenizing both capacity and pricing decisions in a single-product system, Wu and Wu (2015) argued that a rm can use a price discount to achieve demand postponement under P S. Therefore, the rm can full customer orders for the probabilistic product after satisfying the spot demand. Zhang et al (2016) simulated the demand reshape and demand substitution eect of P S. In a newsvendor system with two specic products and one probabilistic product, the retailer can achieve demand substitution between the specic products and the probabilistic product by charging a lower price for the option to satisfy the demand for the probabilistic product later. They found that this strategy can benet the retailer with a higher prot and lower inventory through combating demand uncertainty.…”
Section: Probabilistic Sellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Endogenizing both capacity and pricing decisions in a single-product system, Wu and Wu (2015) argued that a rm can use a price discount to achieve demand postponement under P S. Therefore, the rm can full customer orders for the probabilistic product after satisfying the spot demand. Zhang et al (2016) simulated the demand reshape and demand substitution eect of P S. In a newsvendor system with two specic products and one probabilistic product, the retailer can achieve demand substitution between the specic products and the probabilistic product by charging a lower price for the option to satisfy the demand for the probabilistic product later. They found that this strategy can benet the retailer with a higher prot and lower inventory through combating demand uncertainty.…”
Section: Probabilistic Sellingmentioning
confidence: 99%
“…The gure of the probabilistic product was taken in a retail store in Japan. probabilistic product in P P S. Some operational studies on P S endogenize the inventory decision and explore the benets of adopting P S for inventory management through postponing the delivery of the probabilistic product (Petrick et al, 2012;Gönsch and Steinhardt, 2013;Gallego and Phillips, 2004;Wu and Wu, 2015;Fu et al, 2017), dynamic allocation depending on inventory (Elmachtoub and Wei, 2015), or demand substitution (Zhang et al, 2016). However, the above literature considers virtual probabilistic products rather than physical ones.…”
Section: Introductionmentioning
confidence: 99%
“…Convolutional neural networks (CNNs) are a type of deep learning and have been successfully applied in many fields, including computer vision [25,26] and natural language processing. [27,28] In a CNN, high-level features are extracted from lowlevel features by sliding the convolution kernel over the original data. In the context of Raman spectroscopy, the convolution kernel can process several Raman data points simultaneously, allowing the Raman offset to be recognized.…”
Section: Introductionmentioning
confidence: 99%
“…Out-of-stock replacement strategies encourage consumers to choose to purchase another acceptable and available product in the face of product out-of-stocks, thereby reducing the mismatch between retailer inventory and consumer demand [1]. The probabilistic sales strategy uses the retailer's existing products to create a probabilistic product with certain attributes hidden in a certain proportion [2][3][4]. By encouraging consumers to abandon the purchase of certain products, they choose to purchase low-priced but random probabilistic products to reduce inventory and A mismatch between requirements.…”
Section: Introductionmentioning
confidence: 99%